A basin‐wide carbon‐related proxy dataset in arid China - Yu Li; Yaxin Xue; Mingjun Gao; Zhansen Zhang; Simin Peng; Junjie Duan (Geoscience Data Journal)
Abstract Closed basin accounts for about one‐fifth of the global land area and is an important part of the global terrestrial carbon cycle. Due to its relatively close geographical environment and independent carbon cycling system, it is an ideal place to study regional carbon cycling. Here we present a carbon‐related proxy dataset for the Shiyang River Basin in the eastern part of the Hexi Corridor. The dataset collected carbon‐related indicator data for 997 sediment samples from 14 profiles, 92 surface sediment samples and 25 groundwater samples. It includes total nitrogen (TN), total organic carbon (TOC), inorganic carbon (IC), carbon‐nitrogen ratio (C/N), organic carbon isotopes (δ13Corg), carbonate carbon isotopes (δ13Ccarb), oxygen isotopes (δ18O) and other proxy indicator data, as well as profile and groundwater age data. These data will play an important role in studying organic carbon sinks, inorganic carbon sinks, carbon cycling processes and environmental changes in the closed basin. This dataset can be downloaded from https://doi.org/10.5281/zenodo.10252702.